Sustainable Luxury and Consumer Purchase Intention: A Systematic Literature Review - Luming Zhao; Jiaxi Peng; Shubin Yu (SAGE Open, 2023)
In the last decade, the relationship between sustainable luxury and consumer purchase intention has been gradually noticed by researchers. However, a systematic review of the literature on this topic has not been conducted. The purpose of this study was to collect literature and analyze the current state of research related to sustainable luxury and consumer purchase intention. Based on the Scopus and Web of Science database, this systematic review used a multistep process to ensure the traceability and reliability of the findings. A content analysis shows that sustainable luxury can be presented through four perspectives (raw materials, recycling and reproduction, social media and advertising (AD) strategies, and corporate social responsibility (CSR) and brand promise) in contrast with common luxury goods. In addition to consumer purchase intention, consumer attitude and word-of-mouth (WoM) advertisements were also evaluated as dependent variables. The relationship between the effect of sustainable luxury and consumer purchase intention is multifaceted, and five types of factors are summarized. The results of this review indicate that the related epistemology has been strongly advanced, and luxury brands should approach the topic of manufacturing and retail sustainability on a case-by-case basis and measure whether it translates into better purchasing behavior. The practical implications for luxury retail are discussed.